OVERVIEW PERBANDINGAN TEKNOLOGI ALTERNATIF AKTIF DAN PASIF DALAM PENGELOLAAN AIR ASAM TAMBANG - Shahensah Anand Anggian Rambe; Nurkhamim (Retii, 2020)
ABSTRACT The formation of a metal-rich acid solution known as Acid Mine Drainage (AMD) is a common problem associated with mineral and coal mining in Indonesia. AMD is formed when sulfide minerals such as pyrite (Fe2S) are found to be mixed with coal or overburden in direct contact with oxygen and water during the operational and post-mine closure phases. Therefore, the management of acid mine drainage (AMD) needs to be done so that the water that comes out of the mining area that enters the water does not pollute the environment. Alternative AMD management is generally divided into two, namely active technology and passive technology. The author conducted a comparison of several literatures to analyze active and passive alternative methods, and determine the factors that influence pH changes during treatment. From these results it was found that the selection of the appropriate AMD management method depends on the level of efficiency in the processing of water chemical properties including pH, metal and sulfate concentrations in minimizing costs and risks to the environment. Keywords: Acid mine drainage, active alternative, passive alternative